Study of the Impact Energy Releasing Characteristics of Al/PTFE/W Energetic Jets - Fuhai Li; Hantao Liu; Yanwen Xiao (Shock and Vibration)
Compared with traditional jets, energetic jets have more efficient damage effects. To study the reaction characteristics of polytetrafluoroethylene- (PTFE-) based energetic jets under impact loading, the static mechanical properties of Al/PTFE/W composite energetic materials are studied by using a universal testing machine at a strain rate of 0.01 s−1, and the dynamic mechanical properties are tested on a slip Hopkinson pressure bar (SHPB) system at a strain rate of 1000∼5500 s−1. A dynamic energy acquisition system is established to quantify the energy generated by the response of the Al/PTFE/W energetic jets to impact targets. The effects of the material proportion and impact energy on the mechanical and energy release properties of the Al/PTFE/W energetic jets are analyzed. The results show that the Al/PTFE/W composite has an obvious strain rate effect. As the W content in the composite increases, the yield strength and compressive strength of the material increase gradually, but the strain at break decreases. When the W content is 45%, the peak pressure, total release energy, pressure platform duration, and total pressure duration of the Al/PTFE/W energetic jets are the highest. As the impact energy increases, the pressure peak and energy release values of the energetic jets increase. At an impact energy threshold of 106.1 MJ/m2, the chemical reaction of the Al/PTFE/W (45%) energetic jets is saturated. The results provide a theoretical and experimental basis for the application of energetic jets.